Strategi Asesmen Autentik Guru PAI dalam Meningkatkan Prestasi Belajar Siswa di SMP Al Munawwir Sangatta Selatan - Muhammad Nabil; Anggra Prima; Abdul Kadir (Civiliza Publishing, Indonesia., 2026)
This study examined the authentic assessment strategies used by Islamic Religious Education (PAI) teachers to improve student learning achievement at SMP Al Munawwir Sangatta Selatan. The research employed a descriptive qualitative field-study design. Data were collected through classroom observation, semi-structured interviews with PAI teachers, the principal, and selected students, as well as documentation of assessment instruments and student work. Data analysis followed the stages of data condensation, data display, and conclusion drawing, while trustworthiness was strengthened through source, technique, and time triangulation. The findings showed that authentic assessment was implemented systematically from planning to follow-up by aligning assessment techniques with learning objectives, subject matter, and student characteristics. Teachers used attitude observation, written and oral tests, worship practice, Qur’an and prayer memorization, presentations, group discussions, projects, portfolios, self-assessment, and peer assessment. These strategies enabled teachers to evaluate cognitive, affective, and psychomotor domains more comprehensively and encouraged students to become more active, responsible, confident, and capable of applying religious knowledge in practical contexts. Supporting factors included clear learning objectives, teacher readiness, varied learning methods, student participation, school support, and available instructional media. Inhibiting factors involved limited time, complex assessment administration, student heterogeneity, uneven participation, and insufficient facilities and training. Teachers addressed these constraints through systematic planning, clear rubrics, phased assessment, instructional technology, continuous guidance, and school-based professional development. The study concludes that authentic assessment contributes positively to meaningful PAI learning and student achievement when supported by coherent planning, valid instruments, active student involvement, and sustained institutional support.